Exploring the Link Between Adolescent Risk Attitudes and Fear of Failure: A Preliminary Study - Chakraborty, Soumen (Journal of Research in Vocational Education, 2025)
The study assesses the relation between individual risk attitudes and fear of failure. We measured risk attitudes using the risk attitude scale (Weber and Betz, 2002) and fear of failure using the Performance Failure Appraisal Inventory (Conroy et al., 2002).51 students of ages 14 - 18 years took part in the survey where they completed these two questionnaires with slight modifications. The individual scores were averaged and Cronbach's alpha test was employed to test internal reliability. Pearson's correlation and linear regression analysis was done keeping fear of failure as the independent variable. The questionnaires had good internal reliability. The correlation and regression analysis both indicated a moderate positive relation but the p - values were higher than the standard 0.05 so the relation was not considered statistically significant. The findings motivate us to conduct further research on the topic with a larger sample size to explore the relation more deeply which is imperative to human decision making.